The role of women in the good governance of Semnan in the corona and post-corona era - Mehdi Asghari; Zeinab Karkehbadi; Abbas Arghan (تحقیقات کاربردی علوم جغرافیایی)
In recent decades, good urban governance has been proposed as the most effective, least expensive, and most sustainable method for managing the complex and multi-level systems of modern cities. The centrality of this approach in urban management is based on democratic and egalitarian development, aiming to involve all interested and influential stakeholders in the administration of cities while addressing their diverse needs. On the other hand, women, as one of the main and most influential social groups in urban life, play a prominent role in city administration. Therefore, the purpose of this article is to examine the role of good urban governance during and after the COVID-19 pandemic, with a focus on the women’s status in Semnan. From the perspective of its objective, this research is practical, and in terms of data collection, it is descriptive-survey. A questionnaire was used to collect data and information for this study. The statistical population of the research consists of the citizens of Semnan, with a population of 185,129 people. The sample size was calculated using Cochran's formula, resulting in 383 participants. To analyze the data, single-sample t-tests and multivariate linear regression were employed. Finally, to generalize the results from the sample to the statistical population, structural equation modeling was conducted using Lisrel software. The results of the one-sample t-test showed that the t-values for each of the research variables, with averages lower than the theoretical mean, were negative. This indicates that the dimensions of good urban governance in Semnan, as well as the situation of women in the city, are not in a favorable state. Additionally, the results of structural equation modeling in Lisrel software revealed that the justice variable has the strongest and most significant relationship with good urban governance. Finally, the survey results demonstrate that it is impossible to achieve good urban governance without defining and explaining the practical role of women, who represent half of the city's population and are one of the most important and influential groups in city administration.